2019
DOI: 10.12991/jrp.2019.123
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometry, potentiometry and HPLC in determination of acidity constant for Cabergoline and Tadalafil

Abstract: Acidic dissociation constant (pKa) is an important physicochemical parameter in absorption, dissociation and elimination mechanisms of drugs in body. Various analytical methods are utilized for the determination of pKa values of pharmaceutical active ingredients, and potentiometry, spectrophotometry and HPLC are the most common methods. Cabergoline is dopaminergic ergoline derivative having a powerful and long-term prolactin reducing effect, which is used for the treatment of Parkinson disease. Tadalafil leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The main objective of chromatographic method is to develop a single RP-HPLC method for accurate quantification of Silodosin and Tadalafil. After detailed literature survey Silodosin available with two pKa (pKa1: 4.03, Nindoline ring and pKa2: 8.53, N-ethylaminopropyl group) [15]. The pKa values for Tadalafil were found to be 3.52 by potentiometry and 3.44 by spectrophotometry [16].…”
Section: Development and Optimization Of Methodsmentioning
confidence: 99%
“…The main objective of chromatographic method is to develop a single RP-HPLC method for accurate quantification of Silodosin and Tadalafil. After detailed literature survey Silodosin available with two pKa (pKa1: 4.03, Nindoline ring and pKa2: 8.53, N-ethylaminopropyl group) [15]. The pKa values for Tadalafil were found to be 3.52 by potentiometry and 3.44 by spectrophotometry [16].…”
Section: Development and Optimization Of Methodsmentioning
confidence: 99%
“…As an analytical application of potentiometric studies, the equivalence point of the produced titration curves was identified using the Gran plot . Sundry Gran plot applications have been published in the literature. The goal of this work was to create a potentiometric process for assessing CAP in tablets directly using a Gran plot which was designed using data from a potentiometric investigation of the complexation equilibrium of CAP with various metal ions, especially Cr 3+ , Fe 3+ , La 2+ , Th 4+ , Co 2+ , Mn 2+ , Pd 2+ , Sr 2+ , Ti 2+ , and Zr 2+ .…”
Section: Introductionmentioning
confidence: 99%